Discussing legal adaptations: perspectives on studying migrants' relationship with law in the host country - Kubal, A (International Migration Institute, 2011)
With immigration becoming a structural feature of nearly all industrialized countries, the twentieth century saw a development of a set of theoretical approaches to study the relationship between immigrants and the legal system of the host country. These frameworks – legal assimilation, legal transnationalism, legal pluralism, legal culture – legal consciousness – have developed largely in isolation from one another, sometimes but not always distinguished by disciplinary boundaries – law, anthropology, sociology, politics, international relations. The aim of this paper is to review and organize the scarce yet fragmented scholarship explaining the migration and law nexus in the context of migrants’ legal adaptations to the new legal environment.